2004
DOI: 10.1177/0011000004267563
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Individuals Seek Conversion Therapy?

Abstract: This study examined the potential influence of religiosity, sexual orientation identity development, and internalized homonegativity on the propensity to seek conversion therapy to change one’s sexual orientation. An Internet sample of 76 women and 130 men who were gay-identified, lesbian-identified, same-sex attracted, and “questioning” was studied. Results indicated that two types of religious orientations, intrinsic and quest, predicted a propensity to seek conversion therapy, although in different directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 56 publications
1
36
0
Order By: Relevance
“…Scores can be used to assign each participant an identity status based on phase(s)/stage(s) in which they earn the highest score(s), producing scores that range from 10 (low) to 70 (high) for each phase. Alpha coefficients for the LIQ-R and GIQ-R subscales have ranged from .47 to .88, with most in the .7 or higher range (Mohr and Fassinger 2000;Porter 1988;Tomlinson and Fassinger 2003;Tozer and Hayes 2004). Within the present study, alphas ranged from .76 to .91 for the four LIQ-R subscales, and from .75 to .81 for the four GIQ-R subscales.…”
Section: Additional Instrumentssupporting
confidence: 41%
See 1 more Smart Citation
“…Scores can be used to assign each participant an identity status based on phase(s)/stage(s) in which they earn the highest score(s), producing scores that range from 10 (low) to 70 (high) for each phase. Alpha coefficients for the LIQ-R and GIQ-R subscales have ranged from .47 to .88, with most in the .7 or higher range (Mohr and Fassinger 2000;Porter 1988;Tomlinson and Fassinger 2003;Tozer and Hayes 2004). Within the present study, alphas ranged from .76 to .91 for the four LIQ-R subscales, and from .75 to .81 for the four GIQ-R subscales.…”
Section: Additional Instrumentssupporting
confidence: 41%
“…The GIQ-R and LIQ-R are 40-item, 7 point-Likert-type scale measures of sexual minority identity development based on McCarn and Fassinger's 1996 model of lesbian identity development. The LIQ and GIQ were developed specifically to assess for developmental stage/phase as uniquely expressed in gay men and lesbian women, and have been used repeatedly in the sexual minority identity literature (Porter 1988;Swann and Spivey 2004;Tomlinson and Fassinger 2003;Tozer and Hayes 2004). The four stages/phases assessed by the GIQ-R and LIQ are: awareness, exploration, deepening/ commitment, and internalization/synthesis.…”
Section: Additional Instrumentsmentioning
confidence: 99%
“…Throckmorton (2002) found religiously motivated change a primary incentive for at least some ''ex-gays,'' as these individuals refer to themselves, a contention frequently supported in the literature (Rosik 2003;Yarhouse and Burkett 2002). Indeed, one study of 206 gay men and lesbians identified negativity toward internalized homosexual attraction as the single mediating variable on the relationship between intrinsic religiosity and propensity to seek conversion therapy (Tozer and Hayes 2004). However, whether such change actually occurs, even when religiously motivated, remains in doubt based on empirical study (Schaeffer et al 2000).…”
Section: The Conversion Therapy Controversymentioning
confidence: 92%
“…Items on this measure, including, "I hate myself for being attracted to other women," "I am proud to be a lesbian," and "I feel bad for acting on my lesbian desires," may reflect lesbian identity developed through an individualistic, Western Judeo-Christian-influenced tradition that emphasizes personal responsibility, sin, and shame in relation to same-sex desires (Tozer & Hayes, 2004;Lease, Horne, & Noffsinger-Frazier, 2005). This finding mirrors the results of Horne et al (2009), in a study where they found a variation from Western-conceptualized internalized homo-negativity among their Russian participants.…”
Section: R-lih-9 (Clc) I Have Respect and Admiration For Other Lesbimentioning
confidence: 99%